Analysis of Factors That Influence Smartphone Purchase Decisions Among Economic Education Students FKIP UNTAN - Anugrah, Gloria Elshanda; Asriati, Nuraini; Okianna, Okianna (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to analyze the factors that influence smartphone purchasing decisions among Economics Education students of FKIP UNTAN. The research method applied is descriptive with a qualitative approach. The data source of this study consists of Economics Education students who have purchased smartphones within the last three years. The results show that personal and psychological factors are the most influential in students’ smartphone purchasing decisions. Personal factors affect purchasing decisions particularly in relation to economic conditions, lifestyle, and functional needs, which drive students to select smartphones based on specifications, price, and practical benefits. Psychological factors influence purchasing decisions through motivation, brand perception, and trust in the product. These two factors are the main considerations that most strongly affect smartphone purchasing decisions among the majority of informants, namely Economics Education students of FKIP UNTAN.